Implementing Digital Media in Early Childhood Education: Teachers’ Practices and Institutional Support in North Jakarta, Indonesia - Muhammad Fadhil Arafat; Ratnawati Prayogi; Alfred Inkiriwang (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The rapid development of digital technology in recent decades has significantly transformed early childhood education, providing opportunities to integrate digital media into learning activities. This study aims to analyze the implementation of digital media-based learning in three early childhood education institutions (PAUD Pelangi, PAUD Cempaka, and PAUD Kemuning 013) in North Jakarta, Indonesia. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation, involving three principals, six teachers, and thirty students. Data analysis followed Miles and Huberman’s model, encompassing data collection, condensation, presentation, and drawing conclusions. Findings reveal that digital media is applied systematically, creatively, and interactively, supporting learning activities related to cognitive, language, socio-emotional, and motor domains. Teachers act as planners, facilitators, and content creators, while institutional support provides access to digital devices and professional development opportunities. Classroom observations and interview findings suggest that multisensory strategies and differentiated learning approaches contribute to children's engagement, participation, and motivation during learning activities. The study provides qualitative insights into digital pedagogy practices in early childhood education and offers practical recommendations for strengthening digital media integration in PAUD settings.